Sistema fotovoltaico autónomo de control de humedad por goteo (2019)
Photovoltaic system for humidity and temperature control, installed on the campus of the Antonio Nariño University, Manizales headquarters, which monitors these parameters, by means of hygrometers and thermocouples, making a comparison with the environment and activating or deactivating irrigation according to the established climatic data for the greater use of the water resource and the growth of the crop in this case of coffee.